PEMANFAATAN TEKNOLOGI PESAWAT NIRAWAK UNTUK IDENTIFIKASI PEMANFAATAN LAHAN MASYARAKAT DI DALAM KAWASAN HUTAN PENDIDIKAN UNIVERSITAS HASANUDDIN - Faiq, Muhammad; JB, Abdul Rachman; Afdal, Muhammad; Arkam, Muh. Iriansyah; Nursaputra, Munajat (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
Drones are unmanned aircraft that are controlled by robotic systems and computer systems remotely by pilots on the ground. Drones are able to see the condition of forest areas such as identifying environmental changes and monitoring large areas, it is difficult and time consuming if carried out using land vehicles or on foot can be done easily by simply flying the drone. The use of drone technology can help the management of the Hasanuddin University Education Forest to solve the problem of forest encroachment from time to time. The educational forest area of ​​Hasanuddin University has an area of ​​1,460.50 ha and there are several lands that have been used by the community. Therefore, in this study, identification of community land use in the Education Forest area was carried out by looking at the results of drone aerial photos. The research variable is the recording of land use in the forest in the form of aerial photographs. The photo recording results are combined using agisoft to produce a perpendicular image with a resolution of 8.2 cm – 20.3 /pix. In the identification of land use, it is done using ArcGIS Software. The results of the study illustrate that community use in the forest is in the form of dry land agriculture and rice fields covering an area of ​​33.3 ha or 19% of the total area of ​​the Bengo-Bengo Education Forest area of ​​Hasanuddin University. The occupation that occurs in the Hasanuddin University Education forest is a claim of ownership over land in the forest area. The use of drone technology can help the management of the Hasanuddin University Education Forest to solve the problem of forest encroachment from time to time.